Political Islam in Southeast Asia : moderates, radicals and terrorists - Rabasa, Angel (Adelphi papers, 2003)
"This Paper provides a short, but comprehensive overview of the evolution of political Islam in Southeast Asia and its implications for the future of the region. It analyses the sources of religious radicalism and provides an up-to-date assessment of the regional terrorist and radical networks."--Jacket